Implementasi Metode Regresi Linier Pada Rancang Bangun Sistem Informasi Monitoring Nutrisi Tanaman Hidroponik Kangkung - Nugroho Setyo Wibowo; Muknizah Aziziah; Eva Rosdiana; I Gede Wiryawan (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
Hydroponics is the cultivation of plants without using soil. Hydroponic flowers, herbs and vegetables are grown in a moist growing medium and supplied with a solution rich in nutrients, oxygen and water. In the application of hydroponics, nutrition is a need that must always be met for plant development where each plant requires different nutrients. Nutrient Film Technique (NFT) is a technique that is often used in hydroponic cultivation. Because in this method the circulation of nutrients contained in the water will always flow through the plant at any time. So that plant growth is faster, because plants get oxygen and nutrients all the time. The NFT technique is said to be an energy-intensive technique, because the water pump will run continuously and still use human power. From these problems, a technological innovation is needed to help overcome the existing problems. Advances and developments in IoT technology can facilitate various kinds of work, including controlling hydroponic systems, so that plant care can be carried out remotely and at any time. Information system is a technology that can be used as remote plant monitoring. Information will be obtained through monitoring devices that will be sent to the information system. The method used in this research activity is linear regression method. This method can determine the nutritional valve opening the next day, so that nutrition can be monitored using the system.